(untitled) (Revista científica Pensamiento y Gestión, 2017)
In a digital age, International Education has undergone several changes. Digital platforms have eased the way students can access to academic information. Therefore, the education industry has implemented tools to effectively adapt business to students’ needs. Digital Marketing and its components have been emerging in Interna- tional Education to improve its business practices. Therefore, institutions have been encouraged to promote these mechanisms and adopt them into their corporate structures. The use of online strategies is an optimal channel to attract students. Digi- tal marketing has turned into the ultimate tool to proactively excel in the competition. To show the results of this deductive research paper, an example of the company Big Choice Group will examine the causes and consequences of implementing Digital Marketing in the International Education industry. This paper will present evidence with an analysis of a model on how a mul- tinational has obtained positive results with the implementation of digital strategies.